Social impact assessment of water pollution : a case study on Bangshi River, Savar - Kabir, Muhammad Rezaul (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.